Ideology and Grand Strategy in the Arab-Israeli Conflict: Syria and Israel, 1963-1973 - Yarnell, Brent E. (Tufts Archival Research Center, 2005)
According to neorealism, states are rational actors whose overriding objective is survival, and who formulate their foreign policies based on calculations of the balance of power. The history of Syrian and Israeli foreign policy, however, demonstrates that ideology often plays an important role in identifying the political objectives states pursue on the international arena as well as the grand strategies they employ. This paper explores Syrian and Israeli foreign policy during the period 1963-1973. This period included the June 1967 Six Day War and the October 1973 War, as well as numerous other violent clashes. The period also saw significant ideological flux in the leaderships of both countries. In Syria, the Ba'ath regime that seized power in 1963 was guided by the vision of Pan-Arabism. The Neo-Ba'ath regime that ruled from 1967-1970 was guided by a leftist revolutionary creed. Hafiz al-Assad, who took power in 1970, was a non-ideological realist. In Israel, the Old Guard Mapai leadership that had governed Israel since the period of the British Mandate gradually gave way to other factions, bringing the radical Ahdut Ha'Avodah party into the governing coalition in 1965, and forming a National Unity Government on the eve of war in 1967 that brought Menachem Begin's right wing Cherut party into the Cabinet. In both countries, the ideologies of competing leadership groups exerted a strong influence on the different grand strategies they developed to meet the international threats and opportunities their countries faced. This paper traces the way that changes in the ideological orientation of the leadership in Syria and Israel during this period influenced the grand strategies those states employed, and traces the effect those grand strategies had in on the Arab-Israeli conflict.